Wind creates crown shyness, asymmetry, and orientation in a tropical montane oak forest - Markham, John (2020)
In a cloud forest dominated by Quercus costaricensis, the gap size between the crowns was consistent and crowns were asymmetrical, being elongated perpendicular to the prevailing wind direction. A wind storm of 20 m/s removed 1.5% of the leaves, con-sistent with the idea that wind abrasion shapes tree crowns.